A nonenzymatic method for cleaving polysaccharides to yield oligosaccharides for structural analysis - Matthew J. Amicucci (Nature Portfolio, 2020)
While mass spectrometry-based proteomics largely relies on digesting proteins into peptides, there is no equivalent strategy for polysaccharide analysis. Here, the authors develop a chemical approach to break down poly- into oligosaccharides and present a workflow to identify polysaccharides by oligosaccharide fingerprinting.